Insect overwintering: physiological and biochemical adaptations to low temperatures - Rozsypal, Jan (Jihočeská univerzita, 2013)
Complex experimental data on insect adaptation for survival at low temperatures, with special reference to overwintering in temperate climate zone, are presented in this thesis. The cold tolerance strategies were examined in four species: the codling moth (Cydia pomonella), the bark beetle (Ips typographus), the red firebug (Pyrrhocoris apterus), and the fruit fly (Drosophila melanogaster). Two of these species, C. pomonella and I. typographus, are serious pests and knowledge on their overwintering biology is of great importance for development of pest management programs. Numerous physiological and biochemical parameters, such as supercooling point, thermal hysteresis between melting and freezing points, survival in supercooled and frozen states, osmolality of hemolymph, water and energy reserves, and detailed metabolomic composition of hemolymph and tissues were studied during cold season in the field-collected animals or analyzed in laboratory-acclimated animals in order to assess the insects' capacity for winter survival.
Insect overwintering: physiological and biochemical adaptations to low temperatures